Biophysical property and broad anti-HIV activity of albuvirtide, a 3-maleimimidopropionic acid-modified peptide fusion inhibitor. - Huihui Chong (PLoS ONE, 2012)
Albuvirtide (ABT) is a 3-maleimimidopropionic acid (MPA)-modified peptide HIV fusion inhibitor that can irreversibly conjugate to serum albumin. Previous studies demonstrated its in vivo long half-life and potent anti-HIV activity. Here, we focused to characterize its biophysical properties and evaluate its antiviral spectrum. In contrast to T20 (Enfuvirtide, Fuzeon), ABT was able to form a stable α-helical conformation with the target sequence and block the fusion-active six-helix bundle (6-HB) formation in a dominant-negative manner. It efficiently inhibited HIV-1 Env-mediated cell membrane fusion and virus entry. A large panel of 42 HIV-1 pseudoviruses with different genotypes were constructed and used for the antiviral evaluation. The results showed that ABT had potent inhibitory activity against the subtypes A, B and C that predominate the worldwide AIDS epidemics, and subtype B', CRF07_BC and CRF01_AE recombinants that are currently circulating in China. Furthermore, ABT was also highly effective against HIV-1 variants resistant to T20. Taken together, our data indicate that the chemically modified peptide ABT can serve as an ideal HIV-1 fusion inhibitor.